Implementation of PSAK 46 in Deferred Tax Reporting and its impact on company profits - Hendra Dwi Prasetyo (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2025)
Financial Accounting Standard PSAK 46 regulates the accounting treatment of income taxes, including the recognition of deferred tax assets and liabilities. This research aims to analyze the implementation of PSAK 46 in deferred tax reporting and its impact on company profits. The research method used is a case study of public companies in Indonesia with quantitative and qualitative data analysis. The research results show that the application of PSAK 46 has a significant effect on the presentation of financial reports, especially in reflecting temporary differences between accounting profit and fiscal profit. In addition, the deferred taxes that arise can affect the reported net profit, either in the form of additions or reductions in the value of taxes that must be paid. With proper implementation, PSAK 46 can increase the transparency and quality of a company's financial reports.